Odpowiedzi

Najlepsza Odpowiedź!
2010-03-31T17:57:57+02:00
6.
a) 2z>12
z>6
b) x<2
c) 3x<6
x<2
d) 4x>-4
x>-1
e) x≥1
f) 5x>-10
x>-2
g) 2x>0
x>0
h) 8x+5<4x+1
4x<-4
x<-1
i) -2x≥-2
x≤1
j) x≤-3

7.
a) 4x-4>8
4x>12
x>3
b) 3x+6<-6
3x<-12
x<-4
c) 3x+6-2<4x-4+5
3x+4<4x+1
-x<-3
x>3
d) 6-4x+6-3x≤0
12-7x≤0
12≤7x
x≥12/7
e) -8a+2-2a+6≥0
-10a+8≥0
-10a≥-8
10a≤8
a≤4/5
f) 8-12x+12-6x>0
20-18x>0
18x<20
x<10/9
g) -6x-2+3x-3<0
-3x-5<0
-3x<5
3x>-5
x>-5/3
h) 10x+9>-6+15x
15>5x
3>x
x<3
i) -8a-2<3-10a
2a<5
a<5/2
j) 4-3y>-8y-8
5y>-12
y>-12/5
k) 6x+3-6≤2-3+9x
6x-3≤9x-1
-2≤3x
x≥-2/3
l) 5-8+12x<10x+5-3
12x-3<10x+2
2x<5
x<5/2
ł) 6x+2-1<7+8x
6x+1<7+8x
-2x<6
x>-3
m) 3-11x≤-3x+6
-8x≤3
8x≥-3
x≥-3/8
n) -20+5x+7<3x+3+2x-3
5x-13<5x
-13<0
nierówność tożsamościowa
o) -3k-3-2k+2>-2k-1
-5k-1>-2k-1
-5k>-2k
5k<2k
k<0
p) 4-12x≥-2x-2
6≥10x
5x≤3
x≤3/5
r) -6x-2+1<-7-8x
2x<-6
x<-3
s) 3x-6-10x+5≥0
-7x-1≥0
7x≤-1
x≤-1/7
t) 7x+7-8x+16<0
-x+23<0
x>23
u) -x+3+2x-2<3x+12
-2x<11
2x>-11
x>-11/2
w) -8w+4-3w-6≥0
-11w-2≥0
11w+2≤0
11w≤-2
w≤-2/11
z) 3y+6+4<-y+14
4y<4
y<1

8.
a) 2x+3>x-2
x>-5
b) 2x-1<x+2
x<3
c) 3(3-4x)<15*6-5(5x-2)
9-12x<90-25x+10
9-12x<100-25x
13x<91
x<7
d) 2x-20>10-15x
17x>30
x>30/17
e) 4y+2-3>12y-4
3>8y
y<3/8
f) 6x-4+2x-3>9
8x>16
x>2
g) 6x-16x+4>-8x-3
-10x+4>-8x-3
-2x>-7
2x<7
x<7/2
h) 4x-3x-6>4+4x
-3x>10
3x<-10
x<-10/3
i) 3y-3<4y-y-3
3y<3y
y<y
nierówność sprzeczna
j) x-6+4x>2x-6+x
5x-6>3x-6
5x>3x
x>0
k) 2x-3+4x-16>18x+18-10
6x-19>18x+8
-12x>27
12x<-27
x<-9/4
l) -x+3-3<-x-6
0<-6
nierówność sprzeczna
ł) -8y+1+8y-1>0
0>0
nierówność sprzeczna
m) 6z+4-4<6z-3-20
0<-23
nierówność sprzeczna
n) 15x+10-6x+3≥15
9x≥2
x≥2/9
o) 20y-8+6y<70y-5y+15
26y-8<65y+15
-23<39y
y>-23/39
p) 48-12p+60≥-12p+9p-6
108-12p≥-3p-6
114≥9p
p≤38/3
r) 8n-8+3n+6≥24
11n≥26
n≥26/11
s) 5x+15+4x-20≤40
9x-5≤40
9x≤45
x≤5
t) 3x+2-6x-3>-9
-3x-1>-9
-3x>-8
3x<8
x<8/3
u) 5a+15-8a-40≥12
-3a-25≥12
-3a≥37
3a≤-37
a≤-37/3
w) 21x-9<7x+21
14x<30
x<15/7
z) 9x-8x<24
x<24

Chyba sie nie pomyliłam ;P
1 1 1